Keanekaragaman Famili Araceae di Kawasan Air Terjun Piala sebagai Dasar Pengembangan Media Poster - Mentari, Mentari; Haruna, Moh. Fahri; Anggo, Sulasmi (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2025)
The aim of this research is to find out the types of araceae families in the Cup Waterfall Area, Banggai Regency, and make them into posters as a biology learning medium. The research period is from July – September 2024. Sampling was taken using roaming techniques and validation questionnaire instruments to determine the quality of the posters. Validation was given to material experts, design experts, and biology education students at Muhammadiyah University of Luwuk. Validation results are analyzed by calculating the average score (X), determining the score range (Ideal Mean and Ideal Standard Deviation) and Ideal Presentation. The results of the research found 15 species from 14 plant genera from the Araceae family in the Cup Waterfall area of ??Banggai district, namely Aglaonema simplex, Alocasia longiloba, Amorphophallus muelleri Blume., Caladium bicolor ‘spotted beauty’, Colocasia esculenta, Epipremnum falcifolium, Epipremnum pinnatum (L.), Homalomena expedita, Pothos scandens L., Rhaphidophora aurea, Schismatoglottis calyptrate, Scindapsus hederaceus, Scindapsus pictus, Spathiphyllum cannifolium, and Syngonium podophyllum. The validation results for poster feasibility based on the validator results were obtained respectively, namely the material expert validator showed the ideal category was valid with an ideal percentage of 72.92 (good), the validity by media design experts showed the ideal category was quite valid with an ideal percentage of 65 (good) and feasibility validation by students shows a valid ideal category with an ideal percentage of 83.09 (Very good).